2020
DOI: 10.1111/1752-1688.12892
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Patterns of Low Streamflow and Precipitation Changes in the Chesapeake Bay Watershed

Abstract: Spatial and temporal patterns in low streamflows were investigated for 183 streamgages located in the Chesapeake Bay Watershed for the period 1939–2013. Metrics that represent different aspects of the frequency and magnitude of low streamflows were examined for trends: (1) the annual time series of seven‐day average minimum streamflow, (2) the scaled average deficit at or below the 2% mean daily streamflow value relative to a base period between 1939 and 1970, and (3) the annual number of days below the 2% thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Changes in precipitation, air temperature, land use, and population growth are expected to have direct impacts on streamflow and on the amount and timing of sediment and nutrient loads delivered to the tidal Bay (Clune & Capel, 2021). Increases in air and water temperature in the Chesapeake Bay watershed have already been documented in prior studies (Rice & Jastram, 2015;Wagner et al, 2017) and increases in streamflow were also observed, with relatively larger increases in the north as compared to the south regions of the watershed (Fleming et al, 2021;Rice et al, 2017). The amount and intensity of precipitation have also increased in the eastern U.S., with relatively larger increases in the heavy rainfalls defined as events in the top 10 percentile (Groisman et al, 2004;Karl et al, 2009;Karl & Knight, 1998;Melillo et al, 2014).…”
mentioning
confidence: 82%
“…Changes in precipitation, air temperature, land use, and population growth are expected to have direct impacts on streamflow and on the amount and timing of sediment and nutrient loads delivered to the tidal Bay (Clune & Capel, 2021). Increases in air and water temperature in the Chesapeake Bay watershed have already been documented in prior studies (Rice & Jastram, 2015;Wagner et al, 2017) and increases in streamflow were also observed, with relatively larger increases in the north as compared to the south regions of the watershed (Fleming et al, 2021;Rice et al, 2017). The amount and intensity of precipitation have also increased in the eastern U.S., with relatively larger increases in the heavy rainfalls defined as events in the top 10 percentile (Groisman et al, 2004;Karl et al, 2009;Karl & Knight, 1998;Melillo et al, 2014).…”
mentioning
confidence: 82%
“…Used to normalize the drought deficit metric. This approach extends the use of the deficit metric used in the Chesapeake Watershed by Fleming et al (2020) and the Delaware River Basin by Hammond and Fleming (2021), allowing for volumetric flow departure calculations…”
Section: Streamflow Drought and Low Flow Calculationsmentioning
confidence: 99%
“…At the regional scale, the change in direction of the flow distribution is consistent whereby minimum flows (minimum and 10th percentile), average flows (mean and median) and high flows (maximum and 90th percentile) tend to be either all increasing or decreasing (Gudmundsson et al, 2019). However, at the catchment scale, variability in the direction of changes has been observed between flow indices (Douglas et al, 2000) and the same flow indicator at different parts of the catchment (Fleming et al, 2020). Recent declines in freshwater flows have been observed in southern Australia (Zhang et al, 2016;Huang et al, 2020), the Mediterranean (Haddeland et al, 2014;Greve et al, 2018), southern Africa (Haddeland et al, 2014) and southern Asia (Mondal and Mujumdar, 2012).…”
Section: Changes In Flow To Estuariesmentioning
confidence: 77%